1997
DOI: 10.1038/39651
|View full text |Cite
|
Sign up to set email alerts
|

Structure at 1.65 Å of RhoA and its GTPase-activating protein in complex with a transition-state analogue

Abstract: Small G proteins of the Rho family, which includes Rho, Rac and Cdc42Hs, regulate phosphorylation pathways that control a range of biological functions including cytoskeleton formation and cell proliferation. They operate as molecular switches, cycling between the biologically active GTP-bound form and the inactive GDP-bound state. Their rate of hydrolysis of GTP to GDP by virtue of their intrinsic GTPase activity is slow, but can be accelerated by up to 10(5)-fold through interaction with rhoGAP, a GTPase-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
348
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(358 citation statements)
references
References 25 publications
10
348
0
Order By: Relevance
“…However, these GTPases can be stimulated by GAPs [38,39] that donate a catalytic arginine in trans to the active site [9,10]. These catalytic arginine residues of trimeric GTPases and GAPs stimulate the GTPase activity by 100-fold [33,34] and 1000-fold [11] respectively, by stabilizing a γ-phosphoryl oxygen and\or the β-γ bridge oxygen in the transition state [9,10,12,13]. Modelling an arginine into the Gly"$ position of the Ras structure in the Ras-GAP complex [10] (Figure 4) has revealed that its guanidinium group can occupy a similar position to that of the catalytic Arg()* of the GAP, with no steric clashes.…”
Section: Figure 4 Molecular Modelling Of An Arg 13 Substitution (Equimentioning
confidence: 99%
See 2 more Smart Citations
“…However, these GTPases can be stimulated by GAPs [38,39] that donate a catalytic arginine in trans to the active site [9,10]. These catalytic arginine residues of trimeric GTPases and GAPs stimulate the GTPase activity by 100-fold [33,34] and 1000-fold [11] respectively, by stabilizing a γ-phosphoryl oxygen and\or the β-γ bridge oxygen in the transition state [9,10,12,13]. Modelling an arginine into the Gly"$ position of the Ras structure in the Ras-GAP complex [10] (Figure 4) has revealed that its guanidinium group can occupy a similar position to that of the catalytic Arg()* of the GAP, with no steric clashes.…”
Section: Figure 4 Molecular Modelling Of An Arg 13 Substitution (Equimentioning
confidence: 99%
“…Structural and biochemical data indicate that the conserved residue Gln'" functions in GTP hydrolysis [5] by positioning the hydrolytic water molecule in alignment with the γ-phosphoryl group of GTP [6][7][8]. The transition-state alignment is stabilized further by interaction with a GTPase-activating protein (GAP) [9,10]. Another important catalytic group is the so-called ' arginine finger ' [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, studies performed in fibroblasts have established that upon activation, the three main members of the Rho family remodel the cytoskeleton, each giving rise to a distinct pattern of F-actin structures. Constitutively active forms of Cdc42 (cell-provided conditions suitable for the elucidation of three-dimensional structures of small GTPases (Rittinger et al, 1997;Nassar et al, 1998). Other studies then revealed that formation of GAPRhoGTPase complexes is independent of aluminium and of the guanine nucleotide, suggesting a role for fluoride distinct from that of a γ-phosphatemimic, formulated in the initial hypothesis (Vincent et al, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…The active form is located on the plasma membrane, and the inactive form, in the cytosol. 44 RhoA activation has been shown to affect cell fusion and syncytia formation after infection with paramyxoviurses such as respiratory syncytia virus 45 and Hendra virus. 25 RhoA is regulated by heat shock proteins: HSP90 is required for RhoA activation in thrombin-induced signaling to cytoskeleton, and the activation of RhoA could be specifically inhibited by GA in this reaction.…”
Section: Combining Measles Virus With Heat Shock Protein Inhibitors Cmentioning
confidence: 99%